A review on ergonomics factors determining working in harmony with exoskeletons - Halim, Isa; Mahadzir, Muhammad Nadzirul Izzat; Abdullah, Zulkeflee; Zainal Abidin, Muhammad Zaimi; Muhammad, Mohd Nazrin; Saptari, Adi (Universiti Putra Malaysia Press, 2023)
Exoskeletons are wearable devices that can enhance human strength and are used in various fields, such as healthcare and the manufacturing industry. However, poorly designed exoskeletons can strain the muscles and cause injuries to users. The objectives of this review paper are to review the ergonomics factors that contribute to a harmonious user-exoskeleton interaction and to explore the current trends, challenges, and future directions for developing ergonomically designed exoskeletons. In this review, 102 relevant papers published from 2015 to 2023 were retrieved from Web of Science, Scopus, and Google Scholar. These papers were considered in the analysis for gathering relevant information on the topic. The authors identified six ergonomics factors, namely kinematic compatibility, contact pressure, postural control, metabolic cost, cognitive workload, as well as task demands and workplace conditions, that can influence the interaction between users and exoskeletons. By understanding and addressing these ergonomics factors during the design and development process, exoskeleton designers can enhance the user experience and adoption of the devices in daily living activities and industrial applications